Sphingomyelin and phosphatidylcholine contrarily affect the induction of apoptosis in intestinal epithelial cells - Leucht K; Fischbeck A; Caj M; Liebisch G; Hartlieb E; Beneš, Petr; Fried M; Humpf HU; Rogler G; Hausmann M (Molecular nutrition & food research, 2014)
SCOPE: The major alimentary sources for the plasma membrane lipid sphingomyelin (SM) are dairy products, eggs, and meat. We recently reported that the SM metabolite ceramide induces cathepsin D mediated apoptosis in murine intestinal epithelial cells (IECs) and increases inflammation in acute colitis. We investigated the impact of SM and phosphatidylcholine on apoptosis in human IECs and point out BH3-interacting death agonist (BID) as link between cathepsin D and apoptosis. METHODS AND RESULTS: HT-29 and isolated human IECs were stimulated with SM or phosphatidylcholine. SM treatment resulted in increased apoptosis. Phosphatidylcholine showed contrary effects. Western revealed higher amounts of cathepsin D and BID activation upon lipid stimulation. Western blotting revealed BID activation through SM in both an induced and a spontaneous mouse model of colitis. CONCLUSION: Dietary phospholipids may induce or abolish apoptosis in IECs and seem to play a role in the pathogenesis of inflammatory bowel diseases. This nutritional factor might be considered when evaluating the pathogenesis of inflammatory bowel diseases. Effects of SMase- and SM treatment on inflammation in dextran sulfate sodium induced animal models of colitis and in vitro experiments are discussed as controversial. Variable sources of SM, feeding techniques, and mouse strains might play a role.<ovid:br /><ovid:br />Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: sfingomyeliny; Sphingomyelin Phosphodiesterase; Humans; sfingomyelinfosfodiesterasa; střeva; Cathepsin D; fosfatidylcholiny; buňky HT-29; Intestines; adhezní spoje; Female; Liposomes; buněčná smrt; HT29 Cells; Ceramides; epitelové buňky; lidé; zvířata; Cells, Cultured; myši inbrední C57BL; apoptóza; Epithelial Cells; ženské pohlaví; kultivované buňky; ceramidy; kathepsin D; Colitis; Mice, Inbred C57BL; liposomy; potravní doplňky; Adherens Junctions; protein Bid; Dietary Supplements; BH3 Interacting Domain Death Agonist Protein; Phosphatidylcholines; kolitida; Animals; Cell Death; Sphingomyelins; Apoptosis